Risk factors for mortality from severe community-acquired pneumonia in hospitalized children transferred to the pediatric intensive care unit - Tingting Shi; Chen Chen; Li Huang; Huifeng Fan; Gen Lu; Diyuan Yang; Changan Zhao; Dongwei Zhang (Elsevier, 2020)
Background: Some children hospitalized due to severe community-acquired pneumonia (CAP) require to the pediatric intensive care unit (PICU) because of severe complications. The purpose of this study was to identify the risk factors for mortality in this patient population. Methods: This study evaluated the medical records of 113 hospitalized children with severe CAP, who were transferred to the PICU within 48 h of admission at the Guangzhou Women and Children's Medical Center between 2013 and 2017. Results: The study group consisted of 87 boys (77%) and 26 girls (33%), aged between 1 month and 9 years; 72.6% (82/113) of patients were aged <12 months. The mortality rate was 12.3% (14/113). The most common viral and bacterial pathogens isolated were adenovirus (17.7%, 20/113) and Haemophilus influenzae (8.8%, 10/113). Wheezing, cyanosis, oxygen saturation <90%, Pediatric Early Warning Score (PEWS) >3 on admission, not receiving corticosteroid therapy prior to admission, the need for mechanical ventilation, septic shock, multi-organ dysfunction (MODS), and acute renal failure (ARF) occurring prior to transfer to the PICU, increased alanine aminotransferase (ALT) and aspartate transaminase (AST) levels, and decreased hemoglobin and albumin (ALB) levels were associated with mortality (P < 0.05). Non-survivors were more likely to have an oxygen saturation <90% on admission and lower levels of ALB prior to transfer to the PICU than survivors (P < 0.05). Conclusions: Our results showed that hospitalized children with severe CAP who were transferred to the PICU within 48 h of hospital admission were mainly aged <1 year. Additionally, an oxygen saturation <90% and decreased ALB levels were early prognostic variables independently associated with death.